Assessment of microvascular flow in human atherosclerotic carotid plaques using ultrasound localization microscopyResearch in context - Henri Leroy; Louise Z. Wang; Anatole Jimenez; Nassim Mohamedi; Clément Papadacci; Pierre Julia; Salma El Batti; Jean-Marc Alsac; Jonas Sitruk; Armelle Arnoux; Patrick Bruneval; Emmanuel Messas; et al. (EBioMedicine)
Summary: Background: Neovascularisation of carotid plaques contributes to their vulnerability. Current imaging methods such as contrast-enhanced ultrasound (CEUS) usually lack the required spatial resolution and quantification capability for precise neovessels identification. We aimed at quantifying plaque vascularisation with ultrasound localization microscopy (ULM) and compared the results to histological analysis. Methods: We conducted a prospective, monocentric, study involving patients who were undergoing carotid endarterectomy (CEA) for carotid artery stenosis. The day before CEA ultrasound examination coupled with the injection of microbubbles (MB) as a contrast agent (CEUS) to image the MB circulating within and around the carotid plaque was performed. CEUS images analysis classified patients into 2 groups: absence of neovascularisation (group A) or presence of neovascularisation (group B). ULM was performed by localising and tracking individual MB centres to reconstruct the neovessels structure with a resolution of around 60 μm. Plaques were manually segmented on the images to quantify the number of neovessels and various haemodynamic metrics inside the plaques. Histological analysis of the excised carotid plaque specimens classified patients into 2 groups: absence of neovascularisation (group I) or presence of neovascularisation (group II). Findings: Among the 26 patients included, classification was as follows: group I: n = 8 and group II: n = 18, 18 patients had analysable CEUS images and were classified as follows: group A: n = 10, group B: n = 8. The median (Q1-Q3) number of MB tracked per second inside the plaque was 0.03 (0–0.37) for patients in group I and 0.51 (0–3) for patients in group A versus (vs.) 3.55 (1.26–17.68) for patients in group II and 9.69 (5.83–34.68) for patients in group B (p = 0.00049; p = 0.010 respectively). The length of the MB tracks was 0.02 mm (0–0.16) in group I vs. 0.29 mm (0.22–0.45) in group II (p = 0.0069). The study also showed that flow in the neovessels was greater during systole than during diastole period: 9.38 (1.67–19.17) MB tracked per second vs. 1.35 (0.28–6.56) (p = 0.021). Interpretation: ULM allows the detection of neovessels within the carotid atherosclerotic plaque. Thus, ULM provides a precise picture of plaque neovascularisation in patients and could be used as a non-invasive imaging technique to assess carotid plaque vulnerability. Funding: The study was sponsored and funded by Assistance Publique–Hôpitaux de Paris (CRC 1806 APHP INNOVATION 2018). Co-funding by ART (Technological Research Accelerator) biomedical ultrasound program of INSERM, France.